Implementasi Peraturan Menteri Pendidikan Nasional Nomor 24 Tahun 2007 Tentang Standar Sarana Dan Prasarana di SD Negeri 1 Tripe Jaya Kabupaten Gayo Lues - Said Sala; Isnaini Isnaini; Adam Adam (Mahesa Research Center, 2022)
The purpose of this study was to describe and analyze the implementation of the Regulation of the Minister of National Education Number 24 of 2007 concerning Standards for Facilities and Infrastructure at SD Negeri 1 Tripe Jaya, Gayo Lues Regency and to identify and analyze the inhibiting factors for the implementation of the regulation. The research method used in this research is descriptive with qualitative analysis. Data collection was obtained from interviews, observations, documentation and literature studies. The results of the research that were tested using the theory of Policy Implementation of Donald Van Metter and Carl Van Horn showed that the implementation of the Regulation of the Minister of National Education Number 24 of 2007 concerning Standards for Facilities and Infrastructure at SD Negeri 1 Tripe Jaya had been implemented but not yet optimal: (1) Standards, targets and policy objectives, there is still a lack of comprehensive understanding. (2) Resources, lack of availability of human and financial resources. (3) Characteristics of the Implementing Organization, the workflow guideline for the fulfillment of school facilities and infrastructure has not been established. (4) The attitude of the implementers, there is still a lack of understanding for each implementer, especially in schools. (5) Communication between Related Organizations and Implementation Activities, the need for continuous coordination and socialization between schools and the Education Office. (6) The social, economic and political environment, the need for more concern from the community around the school as well as financial assistance and priority attention from the local government.